Cost Analysis Application of Enhanced Recovery After Surgery (ERAS), is it Beneficial?: a Literature Review - Ihsan, Rizki Muhammad; Romadhon, Yusuf Alam; Praswati, Aflit Nuryulia (Universitas Muhammadiyah Surakarta, 2024)
Background Enhanced Recovery After Surgery (ERAS) is a surgery protocol that focused on the patient. This protocol designed to reduce stress responses and promoting faster recovery to patient. ERAS protocols have been widely used and demonstrating better result in patient outcomes. There is limited information about its economic impact and cost analysis of ERAS. This review aims to analyze the existing literature on the application of ERAS protocol by comparing the cost of patient care with or without ERAS protocol. Methods This study conducted a literature search using electronic research databases over the past ten years. Data was taken from Scopus, analyzed 99 articles using various analysis techniques and supported by the VOS viewer application. The analysis includes observations of research developments, evaluating authors and research subject areas and than analyzed with descriptive statistics to describe the results. Results This study identified ninety nine potential studies published between 2014 and 2024, resulting ten studies for inclusion in the review. The studies identified from various types of surgeries. Nine from ten articles in this review show that application of ERAS protocol resulted in advantage in financial. The advantage of application ERAS protocol to reduce cost of hospitalization due to shorter Length of Stay (LOS), lower mortality and complication rate in patient. Conclusions Application of ERAS protocol provide benefits and efficiency across various types of surgical specialities. Hospitalization costs in ERAS group consistenly lower compared to non-ERAS group.